ANALISIS PENGARUH MOTIVASI KONSUMEN, PERSEPSI KUALITAS, DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA ONLINE SHOP - Lina Wahyuningsih, 0935020706 (Students Journal of Economic and Management, 2013)
The Purpose of this reseach is to analyze the influence ofconsumer motivation, perceived quality and consumer attitudes are shared or partially on purchasing decisions and to analyze which variables are the most dominant in influencing purchasing decisions. The data used in this study is primary data, the questionnaire as a research instrument, which is then processed by the calculation SPSS (Statistical Product and Solutions) version 16. The population in this study were all purchasers and users of consumer products online shop Noval @ thulputhul Semarang. Samples taken are consumers who buy in the online shop Noval @ thulputhul Semarang totaling 100 respondents. Sampling technique in this study using a convenience sampling, ie sampling in accordance with the willingness of respondents to the questionnaire were interviewed. Analysis tool used is multiple linear regression. The results showed that there is a significant positive effect on the motivation of consumers purchasing decisions. There is a significant positive effect between perceived quality on purchase decisions. There is a significant positive effect between a good attitude towards consumer purchasing decisions. Keywords: Consumer motivation, perception of quality, consumer attitudes and purchase decisions